2011
DOI: 10.1017/s136672891100054x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control predicts language switching performance in trilingual speech production

Abstract: This study investigated the role of domain-general inhibitory control in trilingual speech production. Taking an individual differences approach, we examined the relationship between performance on a non-linguistic measure of inhibitory control (the Simon task) and a multilingual language switching task for a group of fifty-six native English (L1) speakers learning French (L2) and Spanish (L3). Better inhibitory control was related to reduced switch costs, but only when switching into or out of the more domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
188
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(240 citation statements)
references
References 34 publications
19
188
15
1
Order By: Relevance
“…This has generally been explained with a larger L1 activation than L2 activation. Whereas such a pattern has also been observed in several studies using mixed language blocks (e.g., de Bruin et al, 2014;Linck et al, 2012;Macizo et al, 2012), there are also studies that observed worse L1 performance than L2 performance in mixed language blocks (e.g., Christoffels et al, 2007;Costa & Santesteban, 2004;Gollan & Ferreira, 2009;Verhoef et al, 2009Verhoef et al, , 2010. Interestingly, this is only the case in production studies, while comprehension studies do not show this pattern (similar to asymmetrical switch costs).…”
Section: When L2 Outperforms L1mentioning
confidence: 58%
See 2 more Smart Citations
“…This has generally been explained with a larger L1 activation than L2 activation. Whereas such a pattern has also been observed in several studies using mixed language blocks (e.g., de Bruin et al, 2014;Linck et al, 2012;Macizo et al, 2012), there are also studies that observed worse L1 performance than L2 performance in mixed language blocks (e.g., Christoffels et al, 2007;Costa & Santesteban, 2004;Gollan & Ferreira, 2009;Verhoef et al, 2009Verhoef et al, , 2010. Interestingly, this is only the case in production studies, while comprehension studies do not show this pattern (similar to asymmetrical switch costs).…”
Section: When L2 Outperforms L1mentioning
confidence: 58%
“…Green, 1998), one would expect faster naming of L1 words than L2 words when asymmetrical switch costs are observed. Some studies have shown exactly this pattern of faster overall L1 than L2 naming and asymmetrical switch costs (e.g., Linck et al, 2012;Macizo et al, 2012). However, there have also been studies that found faster overall L1 than L2 naming and symmetrical switch costs (e.g., Declerck, Koch, & Philipp, 2012;see also de Bruin et al, 2014).…”
Section: Asymmetrical Switch Costs As a Marker For Inhibitionmentioning
confidence: 88%
See 1 more Smart Citation
“…With the exception of one participant, they all started learning English by the age of eleven and they were late bilinguals, in the sense of coming into sustained contact with native speakers only in adolescence. Expected for such a type of bilinguals is the transfer of L1 features into their L2 (Green 1998;Linck et al 2012), which, on the level of sound, results in foreign-accentedness. Interestingly, recent studies have revealed that phonetic cross-linguistic influence (including L1-to-L2 interference) can momentarily increase when a bilingual performs in the bilingual language mode (Grosjean 2008), that is, when both their languages are engaged simultaneously (for references see Sections 1.2 and 1.3).…”
Section: Introductionmentioning
confidence: 99%
“…The main line of research on this topic focused on individual differences in ability to hold an item in working memory, an ability that has been linked to success at text comprehension (Haarmann et al 2003), ambiguity resolution (e. g. Miyake et al 1994), low versus high attachment preference (Swets et al 2007), and foreign language learning (e. g. Baddeley et al 1998). Other lines of research focused on individual differences in inhibition, linking it to success at language acquisition (Darcy et al 2014), degree of competitor activation across and within languages (Festman et al 2010;Gollan et al 2011;Linck et al 2011;Lev-Ari and Keysar 2014;Peperkamp 2013, 2014), and success at inhibiting discourseirrelevant information in either literal (e. g. Gernsbacher and Robertson 1995;Gernsbacher et al 1990 ) or figurative language (e. g. Chiappe and Chiappe 2007;Kintsch 2001). Working memory has also been shown to influence the ability to integrate different types and sources of information online (Dagerman et al 2006;Federmeier and Kutas 2005;Just and Carpenter 1992;Madden and Zwaan 2006;Pearlmutter and McDonald 1995;Traxler et al 2005).…”
mentioning
confidence: 99%